PENERAPAN DIRECT INTERACTION DALAM PEMBELAJARAN TEMA TANAMAN CIPTAAN ALLAH SUB TEMA TANAMAN SAYUR - Tati Kurniati (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Keagamaan Islam UNUGHA Cilacap, 2022)
Direc interaction learning or direct learning is learning that is directed by many teachers. This strategy is effective for determining information and building skills step by step. It is deductive, specifically designed to develop student learning activities related to aspects of procedural knowledge (knowledge of how to do things) and declaration knowledge (knowledge of something in the form of facts, concepts, principles or generalizations) that are well structured and can be learned step by step.